Peak force, velocity and power before and after a 2000 metres rowing test - Simoes, M.; Veloso, A.; Armada da Silva, P. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The all-out 2000 metre indoor rowing performance (2000m test) consists on a high intensity exercise for which anaerobic energy metabolism contributes importantly. In women, fatigue during maximal rowing strokes partially explains performance of 2000m rowing test1 but it is not totally clear whether performing a 2000m test is actually associated with muscle fatigue. Thus the purpose of this study was to investigate whether performing a self-paced 2000m rowing test induces muscle fatigue, determined from changes in peak force (PF), peak velocity (PV) and peak power (PP) during 10 maximal strokes. Methods Eleven male rowers of both national and international levels (weight 79.8 ± 5.2 kg; height 1.83 ± 0.61 m, age 20 ± 3.1 yrs, mean ± SD) volunteered to participate in this study. All subjects were well accustomed to the performance of indoor 2000m tests. The exercise consisted on two bouts of 10 maximal strokes performed both before (Pre 2000m) and after (Post 2000m) a 2000m rowing test. All tests were carried out with the use of a Concept 2 model-C rowing ergometer with damping factor set at level 3 and calibrated with the drag factor 129. The e - row software (version 4.0) was used to obtain values of pace, velocity and power for each of stroke. Force was measured by a strain gauge (HBM type u9b 2Kn 1mV/V) that was attached to the chain-handle connection. Heart rate was obtained by telemetry (Polar Accurex Plus, Tempele, Finland). The first and last strokes were excluded from analysis, so results respect only strokes 2nd to 9th. Differences between pre and post 2000m test and between strokes were analysed by two-way ANOVA for repeated measures. Repeated contrasts were used to compare consecutive strokes. Significance was accepted at P<0.05. Values are mean ± SD. Results Two way Anova revealed that force, velocity and power production during the 8 maximal strokes were all reduced after the 2000m test (P<0.05). Force declined progressively from the 2nd to the 9th stroke but the magnitude of decrease was the same both pre and post 2000m test. The amount of force produced in the 2nd stroke was 1409 ± 189 N (Pre 2000m) and was 10% lower in the 9th stroke (P<0.05). Velocity increased during the first five strokes and then levelled off with this occurring in a similar way before and after the 2000m test. Maximum velocity was 6.27 ± 0.37 m.s-1 during the 7th stroke of Pre 2000m, and was reduced to 5.94 ± 0.37 m.s-1 during the same stroke after the 2000m test. Power production changes along the 8 maximal strokes resembled those for velocity. In Pre 2000m test, power production increased from 364 ± 87 W in the 2nd stroke to 696 ± 118 W in the 7th stroke. During maximal strokes after the 2000m test, power production was reduced, compared to the values observed before the test, reaching a peak of 593 ± 111 W also in the 7th stroke. See Figure 1. Discussion/Conclusion This study demonstrated that performing a 2000m rowing test diminishes the ability to produce force and power during maximum rowing strokes. This is consistent with the development of muscle fatigue induced by high-intensity rowing for 6-7 min and confers some support to the notion that resistance to muscle fatigue is an important factor determining 2000m indoor rowing performances.